Students as partners in China: Investigating the potentials and possibilities for growing practices across universities - Liang, Yifei; Matthews, Kelly E. (International Journal for Students as Partners, 2021)
There is a small but growing body of literature about engaging students as partners (SaP) in Asian countries. To further collective understanding of learner-teacher partnership practices in China, we invited undergraduate students and academics from three Chinese universities to complete a survey on their involvement in, and sense of importance of, 17 practices that align with SaP activities. The 402 students and 85 academic staff who engaged in the survey reported high levels of agreement about the importance of such practices that foster learner-teacher interactions although levels of involvement were lower. The findings demonstrate that SaP practices are unfolding in Chinese universities with evidence of a desire for growth of such activities. Our findings reveal potentials and possibilities for growing such practices in Chinese universities while raising questions about the underlying drivers and values motivating increased interest in learner-teacher interactions that warrant further qualitative research.